Hutan Nagari and the Negotiations of Indigenous-State Relations in Minangkabau - tamrin, Tamrin; Afrizal, Afrizal; Asrinaldi, Asrinaldi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
Forest management in Indonesia often presents a tension between state-driven conservation objectives and the socio-economic interests of indigenous communities. This study explores how the Hutan Nagari (village forest) scheme serves as a conflict resolution mechanism between indigenous communities and the state, with a focus on Sungai Buluah in West Sumatra. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis involving community members, the Village Forest Management Institution (LPHN), and the provincial forestry agency. The findings reveal a dual pattern of conflict: prior to 2019, vertical and macro-level disputes predominated, rooted in top-down state forestry policies that marginalized local customary rights. Following the implementation of the Hutan Nagari scheme, conflicts shifted to a horizontal and micro-level, involving intra-community negotiations over resource access. Conflict resolution strategies evolved accordingly, from institutional strengthening and enhanced community participation to more nuanced approaches, including problem-solving, yielding, and inaction. These strategies align with sustainable development goals, integrating economic welfare and conservation objectives. This research contributes to the discourse on community-based forest management by highlighting the adaptive nature of conflict resolution mechanisms in pluralistic indigenous settings